Wpływ ingerencji dotykowej na automatyzację głosek u dzieci z dyslalią obwodową (Conversatoria Linguistica, 2019)
The main focus of the article is the methodology of developing and saving sounds inthe treatment of children with peripheral dyslalia. The therapeutic techniques subjected to theexperiment were divided for the purpose of the research conducted into two groups of methods,referred to as interfering and non-interfering here. The main criterion for such a divisionwas the patient’s tactile stimulation or its lack.The theoretical aim of the conducted experiment was the exploration of the impact of theinterfering and non-interfering methods on the correction of articulation skills in preschoolchildren. The research was also supposed to answer the question of whether providing moresensory stimuli (tactile, sensory) affects the effectiveness of the therapy of speech defects.